A survey of criteria used to evaluate applications for small animal surgery residency positions. Issue 3 (21st November 2019) - Fleming, Jeremy T.; Giuffrida, Michelle A.; Culp, William T. N.; Runge, Jeffrey J.
Abstract: Objective: To determine attributes of applicants to small animal surgery residency programs (SRP) that are considered important, favorable, or detrimental according to surgeons at SRP registered with the American College of Veterinary Surgeons (ACVS). Study design: Online survey. Sample population: Residency‐trained surgeons at ACVS‐registered SRP. Methods: An online survey was advertised to eligible surgeons. Respondents anonymously provided information about their professional backgrounds and SRP interview practices and rated candidate attributes in terms of importance during application screening and favorable or detrimental effects during selection or ranking. Responses were compared by respondent practice setting and sex. Results: Surveys were completed by 148 of 289 (51%) invited surgeons. Male and female surgeons were equally represented, and 61% worked in academia. Most respondents' SRP offered in‐person interviews, typically to a select applicant group from whom residents were ultimately chosen. Letters of recommendation were the most influential factor in all phases of application review, particularly when respondents knew the writers. Other critical attributes were academic record, internship reputation, research activity, and indices of interpersonal skills. Nearly all respondents considered multiple prior unsuccessful applications detrimental. Academic respondents emphasized academic performance and academic internships; private practice respondents valued personal contact with applicants and surgical specialty internships. Responses did not differ by self‐identified gender. Conclusion: Surgery residency program surgeons preferred first‐ or second‐time applicants with excellent academic credentials, specific internship and research experiences, and letters of support from trusted colleagues as well as strong interpersonal skills. Clinical impact: Prospective residents can use this information to assess their candidacies, identify potential weaknesses, and prepare competitive applications.